The Influence of Trust, Price, and Service Quality on Online Ojek Service Consumer Satisfaction in Sidoarjo Regency: Pengaruh Kepercayaan, Harga, dan Kualitas Pelayanan terhadap Kepuasan Konsumen Jasa Ojek Online di Kabupaten Sidoarjo - Andriani, Viya; Astuti, Mudji (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of trust, price and service quality on consumer satisfaction, either partially or simultaneously. , and to find out which of the variables Trust, Price and Service Quality have the most significant influence on consumer satisfaction for Go-Jek services based on Go-Food in Sidoarjo city. This research is a descriptive research using quantitative methods. The data collection technique is by distributing questionnaires to 100 consumer respondents who use Go-Food services in the city of Sidoarjo. The technique used in this research is multiple linear regression using SPSS (Statistical Package for Social Sciences) version 22 for windows. The results of this study prove that the trust variable has an effect on consumer satisfaction, the price variable has an effect on consumer satisfaction, and the service quality variable has an effect on consumer satisfaction for Gojek-based Go-Food services in the city of Sidoarjo.